The Effect of Ethical Leadership, Code of Ethics on Integrity Mediated by Job Satisfaction - M. Adhi Makayasa; Tigor Sitorus; Chairul Muriman Setyabudi (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2020)
This study aims to determine the effect of ethical leadership, code of ethics on police integrity mediated by job satisfaction  in Bandar Lampung City Police. Police integrity is a crucial phenomenon, because this is the foundation to improve the performance of individuals and organizations as expected by the Indonesian National Police (POLRI). The number of samples in this study were 250 police officers from five different units in the structure of Bandar Lampung City Police. The sampling method used is purposive sampling and cluster sampling. Structural Equation Model Analysis (SEM) is also used to test the effect of ethical leadership, code of ethics and job satisfaction by placing job satisfaction as a mediating variable on police integrity.In accordance with SEM analysis. This study finds that the code of ethics has an influence on job satisfaction (r = 0.45; p <0.00), and ethical leadership has a significant effect on job satisfaction (r = 0.39; p <0.00). The code of ethics affects the integrity of the police (r = 0.299; p<0.00). Furthermore, ethical leadership has a significant influence on police integrity (r = 0.575; p <0.00). Therefore, it can be concluded that the code of ethics has a strong direct effect on job satisfaction. In addition, job satisfaction has a stronger direct effect (r = 0.24; p <0.05) on police integrity.